FLOODPLAIN DEVELOPMENT IN BUI RIVER DUE TO LAND-USE CHANGE FROM 2004 TO 2015 - Thi Minh Thuy, Doan; Xuan Dung, Bui (Journal of Forestry Science and Technology, 2016)
Floodplains are areas adjacent to rivers or lakes that are subject to recurring inundation. Notwithstanding floodplains play significant roles because of its multi-functions, it is impacted adversely by many factors. This study aims to focus on the floodplain development in Bui river belonging to Hoa Binh province and Hanoi capital regarding possible impacts due to land-use change from 2004 to 2015. The extent of floodplain was determined by using Hydrologic Engineering Centers River Analysis System (HEC-RAS) coupled with HEC-GeoRAS which is a useful tool in ArcGIS. Water surface profile data exported from HEC-RAS simulations were processed by HEC-GeoRAS for floodplain mapping. The result shows that during the study period, the total built-up area which are impervious surface including residential area, industrial zone, transportation system and many public areas increased by 2.89% while the unused land and agricultural land decreased by 5.66% and 3.62% respectively. Although the average rainfall of four selected flood events is nearly equivalent or even decreasing, the water surface elevation increased. The final result provides a quantitative analysis of the correlation between percentage of total impervious area and floodplain area in Bui river basin. This study is one of initial efforts that can be used by local administrations to develop contingency land-use plans in order to minimize the negative influences of flood disasters.